Perkawinan Campuran Antar Etnis Jawa dan Pakpak di Desa Jontor, Kecamatan Penanggalan Kota Subulussalam - Munawiranti Cibro; Sakti Ritonga; Ismail (Ethics and Law Journal: Business and Notary, 2023)
The purpose of this research is to find out the background that influences the occurrence of inter-ethnic marriages, especially the Javanese ethnicity with the Pakpak ethnicity and to see the interactions that occur and how clans can function in the family kinship system of mixed marriages. The research location is Jontor Village, Penanggalan District, Subulussalam City. This research uses functional structural theory proposed by Talcott Parsons. In analyzing the data, researchers used descriptive qualitative methods with data collection techniques of observation, interviews and documentation as well as supporting data types, namely primary and secondary data. The results of this study found that: first, there are several motives for the emergence of Javanese-Pakpak inter-ethnic marriages in Jontor Village, namely: 1) intensive social interaction between ethnicities: 2) stereotyping of other tribes such as Aceh due to trauma from the GAM-RI conflict: 3) Javanese strategies to obtain protection from the majority group: 4) strategies to improve the economy through inheritance. Secondly, the impacts of mixed marriages include: 1) reducing the occurrence of social disharmony, 2) the emergence of a new generation: 3) exchange of experiences: 4) the emergence of a new culture: 5) fading of original cultural values and culture: 5) influence on the successor of the clan. Third, the kinship system used by mixed marriage families is the Pakpak kinship system. Because Pakpak people tend to dominate the mixed marriages that occur. Javanese men who marry Pakpak girls must be willing to be incorporated into the Pakpak kinship system through the Mangain custom as a sign that he has legally entered the Pakpak kinship system.